2016
DOI: 10.1371/journal.pone.0146187
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of a New Low-Dose Stereoradiography System to Perform 2D and 3D Knee Prosthetic Alignment Measurements

Abstract: IntroductionThe EOS stereoradiography system has shown to provide reliable varus/valgus (VV) measurements of the lower limb in 2D (VV2D) and 3D (VV3D) after total knee arthroplasty (TKA). Validity of these measurements has not been investigated yet, therefore the purpose of this study was to determine validity of EOS VV2D and VV3D.MethodsEOS images were made of a lower limb phantom containing a knee prosthesis, while varying VV angle from 15° varus to 15° valgus and flexion angle from 0° to 20°, and changing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…LLRs were made, and 2D measurements and 3D reconstructions were performed for these different positions. It was concluded that 2D alignment measurements differed considerably from the preset angle of the artificial leg, while the 3D reconstructions showed small deviation [ 30 ]. Besides validity, excellent intra- and interobserver reliability has been shown in the same study when performing knee prosthesis alignment measurements using EOS 3D reconstructions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…LLRs were made, and 2D measurements and 3D reconstructions were performed for these different positions. It was concluded that 2D alignment measurements differed considerably from the preset angle of the artificial leg, while the 3D reconstructions showed small deviation [ 30 ]. Besides validity, excellent intra- and interobserver reliability has been shown in the same study when performing knee prosthesis alignment measurements using EOS 3D reconstructions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, postoperative LLRs were taken 6 weeks postoperatively, at which point patients are generally able to apply full weight on their operated leg and can extend the knee. Moreover, the EOS system corrects malpositioning during acquisition, including flexion of the knee [ 30 ]; therefore, the moment of acquisition is not expected to influence our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that limb rotation or foot rotation could significantly affect the outcome [6] [9][11] [15]. The measurement error of hip-knee-ankle (HKA) angle could reach 4-10 degrees or even greater [14] [15]. While the recommended HKA after TKA ranges from -3°to 3°, which represents a proper knee alignment and prosthesis position.…”
Section: Introductionmentioning
confidence: 99%